Strategic Decision Analysis to Accelerate Plug and Abandonment Project at Sumatra Block - Case of Pacific Oil Company (The Indonesian Journal of Business Administration, 2020)
Asset and site restoration become a critical process for any oil and gas exploration and exploitation operation. It is a mandatory for any production operator to ensure the ex-location of an oil or gas well are fully recovered as environmental-friendly habitat. One of the initial process of the asset and site restoration is well’s subsurface plug and abandonment operation. The main objective of subsurface plug and abandonment operation is to set a mechanical barrier (cement plugs) inside and outside wellbore to ensure sealing between each hydrocarbon zones and between hydrocarbon zones to surface. The project team conduct a brainstorm session to gather any ideas how to achieve the management direction. The project team used conceptual framework of why tree analysis and conducted a thorough review to generates the possible alternatives. By conducting a brainstorm session in the team meeting and discussion, there are 5 major elements that may have impact to the project schedule: work program/procedures, organization capability, tools and services, well’s equipment and materials, and environmental. Based on several focus group discussions, it is concluded that the most significant and direct impact on accelerating the plug and abandonment project is by adding new unit to execute the project. To add a new unit, the project team select 3 (three) possible alternatives: Add new rig, Re-allocate workover/well service rig, combine rig and coil tubing unit. There were 3 (three) decision criteria for this process: Project schedule uncertainty, Impact to production, Total cost of action. Then the project team used analytic hierarchy process to compare each alternative and calculate the best alternative for the project execution. The final calculated scores are Add new rig (0.339), Re-allocate workover/well service rig (0.292), combine rig and coil tubing unit (0.369). Keywords: Oil and Gas, Drilling and Completion, Plug and Abandon, Decommissioning, Barrier, Subsurface Integrity, Brainstorming, Why Tree Analysis, Analytic Hierarchy Process, Rig, Coil Tubing Unit, Cycle Time.